2002
DOI: 10.1016/s105913110200256x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of probable relationship between Toxoplasma gondii and cryptogenic epilepsy

Abstract: Purpose: Cryptogenic epilepsy, defines a group of epilepsy syndromes for which an aetiology is unknown but an underlying brain disease is suspected. We selected patients in this subgroup of epilepsy and investigated the sero-positivity rate for anti-Toxoplasma IgG antibodies by Enzyme Linked Immunosorbent Assay (ELISA). We investigated the probable relationship between Toxoplasma gondii and cryptogenic epilepsy. Methods: We selected 50 patients with cryptogenic epilepsy, 50 patients with known cause epilepsy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…2 The tissue cysts remain largely quiescent for the life of the host, but can reactivate and cause life-threatening toxoplasmic encephalitis in immunocompromised patients, such as those with AIDS, neoplastic diseases and organ transplants. 3,4 In immunocompetent individuals, recent studies suggested that T. gondii is an important cause of cryptogenic epilepsy, 5,6 and is likely involved in the etiology of schizophrenia. 7,8 The tissue cyst is not affected by any of the current drug treatments and it has been generally regarded as untouchable.…”
Section: ؉ Immune T Cells Possess a Potent Activity To Remove The Cysmentioning
confidence: 99%
“…2 The tissue cysts remain largely quiescent for the life of the host, but can reactivate and cause life-threatening toxoplasmic encephalitis in immunocompromised patients, such as those with AIDS, neoplastic diseases and organ transplants. 3,4 In immunocompetent individuals, recent studies suggested that T. gondii is an important cause of cryptogenic epilepsy, 5,6 and is likely involved in the etiology of schizophrenia. 7,8 The tissue cyst is not affected by any of the current drug treatments and it has been generally regarded as untouchable.…”
Section: ؉ Immune T Cells Possess a Potent Activity To Remove The Cysmentioning
confidence: 99%
“…It has been postulated that T. gondii infection is associated with cryptogenic epilepsy (epilepsy of unknown causes) in endemic areas (Tenter et al, 2000;Stommel et al, 2001;Yazar et al, 2003;Zibaei et al, 2011). The proposed mechanism through which T. gondii causes epilepsy has been described in details elsewhere (Stommel et al, 2001).…”
Section: Toxoplasma Gondii and Toxoplasmosismentioning
confidence: 99%
“…However, evidence from case control and ecological studies from other parts of the world reports a possibility that cryptogenic epilepsy may be a consequence of latent toxoplasmosis infections (Tenter et al, 2000;Stommel et al, 2001;Yazar et al, 2003;Zibaei et al, 2011). In support of this hypothesis, observational studies have reported a decline in incidence of cryptogenic epilepsy and toxoplasmosis with time (Potasman et al, 1995;Yazar et al, 2003;Schuster & Visvesvara, 2004). Mostly as a consequence of improved nutrition and personal hygiene and public health education to risk groups (Stommel et al, 2001).…”
Section: Toxoplasma Gondii and Toxoplasmosismentioning
confidence: 99%
“…The released parasites go through different parts of the host body and enter all nucleated cells of the body, especially cells of the nervous system, which causes necrosis and creates massive lesions (7)(8)(9)(10). Most immunocompetent individuals carrying the parasite cysts, especially in the central nervous system, have a model of chronic asymptomatic common infection (11,12). There are several reports that show chronic Toxoplasma infection may alter human behavior.…”
Section: Introductionmentioning
confidence: 99%